Sounder - Armstrong, William H. (William Howard), 1914-1999.; Barkley, James (New York : HarperTrophy, 1972)
A young African-American boy learns the pain of humiliation and anger when his father is given an unjust jail sentence for stealing a ham from a white man. Learning to read and to discover that things do not die, but become part of other things, brings the youngster new hope.
"Trophy Newbery"--Cover.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Booklist, April 2009.
Child Study Children's Book Committee, January 2010.
Keywords: African Americans -- Fiction; Poverty -- Fiction; African Americans -- Fiction; Poverty -- Fiction